Preclinical Modeling of KIF5B-RET Fusion Lung Adenocarcinoma - Huang, Qingling (Mol Cancer Ther, 2016)
RET fusions have been found in lung adenocarcinoma, of which KIF5B-RET is the most prevalent. We established inducible KIF5B-RET transgenic mice and KIF5B-RET-dependent cell lines for preclinical modeling of KIF5B-RET-associated lung adenocarcinoma. Dox-induced CCSP-rtTA/tetO-KIF5B-RET transgenic mice developed invasive lung adenocarcinoma with desmoplastic reaction. Tumors regressed upon suppression of KIF5B-RET expression. By culturing KIF5B-RET-dependent BaF3 (B/KR) cells with increasing concentrations of cabozantinib or vandetanib, we identified cabozantinib-resistant RET(V804L) mutation and vandetanib-resistant-RET(G810A) mutation. Among cabozantinib, lenvatinib, ponatinib, and vandetanib, ponatinib was identified as the most potent inhibitor against KIF5B-RET and its drug-resistant mutants. Interestingly, the vandetanib-resistant KIF5B-RET(G810A) mutant displayed gain-of-sensitivity (GOS) to ponatinib and lenvatinib. Treatment of Dox-induced CCSP-rtTA/tetO-KIF5B-RET bitransgenic mice with ponatinib effectively induced tumor regression. These results indicate that KIF5B-RET-associated lung tumors are addicted to the fusion oncogene and ponatinib is the most effective inhibitor for targeting KIF5B-RET in lung adenocarcinoma. Moreover, this study finds a novel vandetanib-resistant RET(G810A) mutation and identifies lenvatinib and ponatinib as the secondary drugs to overcome this vandetanib resistance mechanism.